Late Carboniferous postglacial brachiopod faunas in the Southwestern Gondwana margin - Cisterna, Gabriela Adriana (2016)
The glaciomarine sediments related to the Late Paleozoic Ice Age (LPIA), have an excellent stratigraphic record in Argentina, particular those associated to the Late Carboniferous glacial episode identified along the southwestern margin of South America: Bolivia (Tarija Basin), west central Argentina (Calingasta-Uspallata Basin) and Patagonia (Tepuel-Genoa basins). The aim of this contribution is mainly a biostratigraphy update of the carboniferous brachiopod faunas that occur in the earliest postglacial interval (late Serpukhovian-Bashkirian) in the west central Argentina (i.e. Levipustula and Aseptella-Tuberculatella/Rhipidomella-Micraphelia) and its regional correlation with those equivalents in the nearby basins. Components of these faunas are recognized from the Bolivia to Argentine Patagonia and the compositional variations exhibited by them appear to be principally controlled by a paleolatitudinal factor. The affinities showed by the postglacial faunas from the Calingasta-Uspallata Basin and the faunal assemblages that integrate the Lanipustula and Tuberculatella biozones in Patagonia, differ from the strong contrast proposed by other authors, based on the paleogeographical position of Patagonia in the Late Paleozoic. Paleoecological studies focuseon the paleoenvironmental controls related with the glacial dynamic are suggested to understand the complex relationship between these postglacial faunal.